Formulation of Peel-off Gel Mask Preparations Moringa Leaf Extract (Moringa oleifera Lam.) and Fragrant Lemongrass Essential Oil (Cymbopogon nardus L. Rendle) - Adhayanti, Erlina; Arpiwi, Ni Luh; Darsini, Ni Nyoman (Metamorfosa: Journal of Biological Sciences; Vol 9 No 1 (2022)DO - 10.24843/metamorfosa.2022.v09.i01.p10, 2022)
Peel-off gel masks are practical masks, because it can be removed without rinsing with water. Peel-off gel mask useful for clean and tighten facial skin. Moringa leaves and citronella essential oil can be used as masks cause have antioxidant and antibacterial activities that act as anti-aging and anti-acne. The purpose of this study was to determine the combination of citronella essential oil and concentration of moringa leaf extract that produced the best mask. Essential oil was extracted by steam distillation, moringa leaves were extracted by maceration using 96% ethanol. Mask was formulated with 0, 1, 2, and 3% moringa leaf extract. The yield of citronella leaf essential oil was 0.36%±0.07 % w/w. The organoleptic test results showed that all mask formulas were stable during storage. The results of the physical properties test of the mask showed that the F3 formula (combination of 1% Moringa leaf extract and 0.30% lemongrass essential oil) produced the best mask preparation. All mask formulas had homogeneous results and met the standards on the viscosity, pH and dispersibility test, but the F1 formula (positive control) on the adhesion test and the F1 formula (positive control) and the F2 formula (negative control) on the drying time test did not meet the requirements good standard of mask. The F3 mask formula is preferred by probandus and all mask formulas do not cause irritation to the skin. Keywords : Cymbopogon nardus L. Rendle, gel, mask, Moringa oleifera Lam., Peel-off